2019
DOI: 10.1186/s42408-019-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of fire characteristics affect animal responses in pyric landscapes

Abstract: Background: Behavioral responses are the most immediate ways animals interact with their environment, and are primary mechanisms by which individuals mitigate mortality risk while ensuring reproductive success. In disturbancedriven landscapes, animals must adjust behaviors both spatially and temporally to maximize individual fitness. Prescribed fire is an important ecosystem driver in many coniferous forests, as fire cycles nutrients, creates spatially heterogeneous distributions in quantity and quality of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…The lack of support for landscape metrics may be due to the resolution of land cover data that masked important, local‐scale heterogeneity within land cover classes. For example, recent work in the southeastern United States has indicated that wild turkeys readily use mature pine forests wherein females select stands that have been recently burned (Kilburg et al 2014, Streich et al 2015, Yeldell et al 2017 a , Cohen et al 2019, Wood et al 2019), but site‐specific spatial and temporal information on fire histories were necessary to evaluate and draw such conclusions. Our inability to capture potential differences in reproductive success relative to landscape metrics highlights the limitations of using coarse‐grained remotely sensed data products in landscapes dominated by a single cover type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of support for landscape metrics may be due to the resolution of land cover data that masked important, local‐scale heterogeneity within land cover classes. For example, recent work in the southeastern United States has indicated that wild turkeys readily use mature pine forests wherein females select stands that have been recently burned (Kilburg et al 2014, Streich et al 2015, Yeldell et al 2017 a , Cohen et al 2019, Wood et al 2019), but site‐specific spatial and temporal information on fire histories were necessary to evaluate and draw such conclusions. Our inability to capture potential differences in reproductive success relative to landscape metrics highlights the limitations of using coarse‐grained remotely sensed data products in landscapes dominated by a single cover type.…”
Section: Discussionmentioning
confidence: 99%
“…forests are the dominant cover type in the Southeast, and on public lands, may be maintained via prescribed fire every 3–5 years (Carter and Foster 2004). Fire plays an important role in creating suitable nesting conditions for wild turkeys (Cohen et al 2019). Consequently, ground vegetation conditions on public lands in the Southeast may be considerably different from those in agro‐forested regions of the Northeast and Midwest, and landscape metrics identified in northern studies may not be useful for turkey management in southern forests.…”
mentioning
confidence: 99%
“…(2014) and Cohen et al. (2019) both recently used FPT values to infer the scale at which wild turkeys ( Meleagris gallopavo ) reacted to changes within their environment. We used similar methodology to infer the scale at which coyotes responded to their environment.…”
Section: Methodsmentioning
confidence: 99%
“…We used behavioral change‐point analysis (BCPA) to model coyote behavior (Gurarie et al., 2009) using methods outlined in Cohen et al. (2019). The BCPA is a likelihood‐based method that identifies changes in movement patterns using locational time‐series data.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, previous researchers have already reported how timing of fire influences turkey behavior (Little et al 2016; Yeldell et al 2017 a , b , c ; Wood et al 2018). Likewise, our model did not account specifically for spatial variations in fire intensity across burn units, although Cohen et al (2019) detailed influences of fire severity within burn units on turkey movements, and we used those data in our analyses as detailed herein (ODD in Supporting Information). We also recognize our model used landscapes represented by burn units with different fire‐return intervals arranged systematically in a checkerboard fashion, rather than randomly distributing fires or otherwise distributing units with different fire‐return intervals across the landscape.…”
Section: Discussionmentioning
confidence: 99%